Patients' use of smartphone apps for health record access in 2019: A cross-sectional study. (October 2022) - Nguyen, Oliver T.; Renfro, Chelsea P.; Hughes, Jonathan; Kumar, Sajeesh; Alishahi Tabriz, Amir; Hong, Young-Rock; Hanna, Karim; Feldman, Sue S.; Schlossman, David M.; Turner, Kea
Highlights: National-level data were used to estimate the prevalence of patients' use of smartphone apps to access their patient portal. About 39% of patients reported use of a smartphone app to access their patient portal. Differences in smartphone app use to access the patient portal were observed by age, race/ethnicity, household income, and use of smartphone-only internet (i.e., only source of internet is the smartphone). Abstract: Introduction: The 21st Century Cures Act has expanded patients' access to portals through smartphone applications (apps). To date, the prevalence of patient portal smartphone apps use is unclear, especially on a national scale. Methods: Using the 2019 Health Information National Trends Survey, we assessed factors associated with patient portal adopters accessing their records through a smartphone app. Multivariable logistic regression models were conducted and we reported results using predicted probability. Results: Across a weighted sample of 75, 324, 288 respondents, 39 % reported using a smartphone app to access their health records. Adults with smartphone-only internet (40.0 %; 95 % CI: 35.4–33.3) were more likely to use a smartphone app compared to adults with home internet access (30.6 %; 95 % CI: 27.9–44.7). Conclusions: Optimizing the implementation and delivery of patient portal content via smartphone apps may improve their reach to patients.